Three-Dimensional Characterization of the Normal Human Parafoveal Microvasculature Using Structural Criteria and High-Resolution Confocal Microscopy - An, Dong; Yu, Paula; Freund, K. Bailey; Yu, Dao-Yi; Balaratnasingam, Chandrakumar (Investigative ophthalmology & visual science, 2020)
To use structural criteria to reconcile the three-dimensional organization and connectivity of the parafoveal microvasculature. The parafoveal microvasculature was perfused and labeled in 16 normal human donor eyes for lectin, alpha smooth muscle actin, and filamentous actin. Established structural criteria gathered using confocal microscopy, including vessel diameter, endothelial cell morphology, and presence/density of smooth muscle cells, were used to differentiate arteries, arterioles, capillaries, venules, and veins. Three-dimensional visualization strategies were used to define the connections between retinal arteries and veins within the superficial vascular plexus (SVP), intermediate capillary plexus (ICP), and deep capillary plexus (DCP). The parafoveal microvasculature has two different inflow patterns and seven different outflow patterns. The SVP and ICP were connected to retinal arteries by arterioles. Inflow into the DCP occurred only via small arterioles (a1; mean diameter, 8.3 µm) that originated from the ICP. Direct connections between the DCP and retinal arteries were not identified. Each capillary plexus formed its own venule that drained independently or in conjunction with venules from other plexuses into a retinal vein at the level of the ganglion cell layer. For the DCP, a1 was significantly smaller than its draining venule (mean diameter, 18.8 µm; P < 0.001). The SVP and ICP of the parafoveal microvasculature have both in series and in parallel arterial and venous connections. Arterial supply to the DCP originates from the ICP, but with direct drainage to the retinal vein. These findings may help to develop an understanding of the pattern of retinal lesions characterizing a myriad of retinal vascular diseases.